Optimized Extraction of Resveratrol from Arachis repens Handro by Ultrasound and Microwave: A Correlation Study with the Antioxidant Properties and Phenol Contents - Leonardo Garcia; Renata Garcia; Georgia Pacheco; Felipe Sutili; Rodrigo De Souza; Elisabeth Mansur; Ivana Leal (The Scientific World Journal)
The vegetal species Arachis repens, commonly known as peanut grass, was studied and, for the first time, we detected the presence of the bioactive compound trans-resveratrol (t-RSV). We compared the efficiency of three different methodologies (conventional maceration [CM], ultrasound-assisted extractions [UAE], and microwave-assisted extractions [MAE]) concerning total phenolics (TP) and resveratrol (t-RSV) content, followed by antioxidant activity (AA) evaluation. By CM, at 1 h, the highest RSV content (1.024±0.036 mg/L) and, correspondingly, the highest DPPH capture (23.90±0.04%) were found. The TP contents, at 1 h, presented the highest value (27.26±0.26 mg/g GAE). By the UAE, the maximum yields of TP (357.18 mg/g GAE) and RSV (2.14 mg/L), as well as, the highest AA (70.95%), were obtained by 5 min after a maceration pretreatment, on the solid-solvent ratio 1 : 40 w/v. For MAE, a central composite rotatable design (CCRD) was applied followed by the FFD design in order to evaluate the statistical effects of four independent variables on the extraction of RSV. The optimal conditions established for obtaining the highest recovery (2.516 mg/g) were 20 min; 90% MeOH aq.; 120 rpm; 60°C; and solid-solvent ratio: 1 : 35 w/v. Relevant correlations were established considering the TP and RSV contents, as well as the AA, corroborating obvious advantages of such techniques in terms of high extraction efficiency in shorter times.